Cottonseed oil composition and its application to skin health and personal care - Gutierrez, Janelle; Komarnytsky, Slavko (Frontiers in Pharmacology, 2025)
The historical use of oils for beauty and hygiene dates back to ancient civilizations. While mineral oil and its derivatives dominated the personal care industry in the 20th century due to chemical stability and low cost, the environmental impact and sustainability concerns have driven a resurgence in the use of vegetable oils. Cottonseed oil derived from Gossypium hirsutum L. (Malvaceae) has been often overlooked in favor of other plant oils, likely due to cotton’s primary use as a fiber crop. Yet cottonseed oil stands out in cosmetics for its beneficial linoleic to oleic acid ratio, which supports skin barrier function, and its rich profile of phytosterols and tocopherols that provide higher oxidative stability and extended shelf life. Cottonseed oil is also adaptable for use in a variety of formulations, offering a lightweight, non-greasy emollient base with potential applications in skin care, hair, and cleansing products. This review highlights cottonseed oil as a potentially underutilized ingredient in the personal care sector and emphasizes the need for further research and development to fully exploit its properties.